A data‐informed system to manage scarce blood product allocation in a randomized controlled trial of convalescent plasma. Issue 12 (26th October 2022) - Li, Na; Zeller, Michelle P.; Shih, Andrew W.; Heddle, Nancy M.; St. John, Melanie; Bégin, Philippe; Callum, Jeannie; Arnold, Donald M.; Akbari‐Moghaddam, Maryam; Down, Douglas G.; Jamula, Erin; Devine, Dana V.; et al.
Abstract: Background: Equitable allocation of scarce blood products needed for a randomized controlled trial (RCT) is a complex decision‐making process within the blood supply chain. Strategies to improve resource allocation in this setting are lacking. Methods: We designed a custom‐made, computerized system to manage the inventory and allocation of COVID‐19 convalescent plasma (CCP) in a multi‐site RCT, CONCOR‐1. A hub‐and‐spoke distribution model enabled real‐time inventory monitoring and assignment for randomization. A live CCP inventory system using REDCap was programmed for spoke sites to reserve, assign, and order CCP from hospital hubs. A data‐driven mixed‐integer programming model with supply and demand forecasting was developed to guide the equitable allocation of CCP at hubs across Canada (excluding Québec). Results: 18/38 hospital study sites were hubs with a median of 2 spoke sites per hub. A total of 394.5 500‐ml doses of CCP were distributed; 349.5 (88.6%) doses were transfused; 9.5 (2.4%) were wasted due to mechanical damage sustained to the blood bags; 35.5 (9.0%) were unused at the end of the trial. Due to supply shortages, 53/394.5 (13.4%) doses were imported from Héma‐Québec to Canadian Blood Services (CBS), and 125 (31.7%) were transferred between CBS regional distribution centers to meet demand. 137/349.5 (39.2%) and 212.5 (60.8%) doses were transfused at hubs and spoke sites, respectively. The mean percentages of total unmet demand were similar across the hubs, indicating equitable allocation, using our model. Conclusion: Computerized tools can provide efficient and immediate solutions for equitable allocation decisions of scarce blood products in RCTs.